The Speaking English problem of Thai Student of Junior high school student at Hadsaithong School - Madeena Dalai Dalai; M Sofian Hadi (Teaching English and Language Learning English Journal, 2023)
This qualitative study aimed to identify the problems faced by students in learning English speaking at Hadsaithong School in southern Thailand, the factors causing these problems, and the solutions that students use to overcome them. The study included 10 high school students, 5 males and 5 females in Grade 9. Internal factors such as motivation, vocabulary, grammar, pronunciation, fluency, shyness, anxiety, and self-confidence were identified as challenges, along with external factors such as the learning environment, teacher motivation, facilities, and lack of opportunities to use English in daily life. The methods students use to solve their English-speaking problems include learning through YouTube, asking English teachers to use English in class, asking fluent friends for help, or ignoring the problems. .